Systemic Inflammatory Response and Chemotherapy Efficacy in Non-Small Cell Lung Cancer: An Analysis of the Platelet-to-Lymphocyte Ratio as a Predictive Biomarker - Sudarto; Ade Pratama Heriansa (HM Publisher, 2025)
Background The variable response to chemotherapy in non-small cell lung cancer (NSCLC) necessitates accessible biomarkers for prognostic stratification. The platelet-to-lymphocyte ratio (PLR), a marker of systemic inflammation, is a promising candidate. This study evaluates the predictive value of pre-treatment PLR for chemotherapy response in an Indonesian NSCLC cohort, a population underrepresented in biomarker research. Methods: A retrospective cohort study was conducted on 59 adult patients with advanced-stage NSCLC at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Patients receiving first-line platinum-based chemotherapy were included. The association between baseline hematological markers and chemotherapy response (Partial Response [PR], Stable Disease [SD], Progressive Disease [PD]) was analyzed using the Kruskal-Wallis test, with Dunn's test for post-hoc comparisons. Receiver Operating Characteristic (ROC) curve analysis was used to determine the predictive accuracy and an optimal cut-off value for PLR. Results: Statistically significant differences in median PLR were found across all response groups (p-value <0.0001). Post-hoc analysis confirmed a graded response, with the PLR of the PD group being significantly higher than that of both the SD and PR groups. ROC analysis demonstrated good predictive accuracy for PLR in discriminating responders (PR) from non-responders (SD+PD), yielding an Area Under the Curve (AUC) of 0.86. A PLR cut-off of 185 was identified, showing high sensitivity and specificity. Conclusion: In this cohort, pre-treatment PLR was a statistically robust predictor of chemotherapy response, with a clear dose-response relationship and good predictive accuracy. PLR reflects the crucial balance between tumor-driven inflammation and host immunity, and its elevation signals a biological state that is resistant to standard chemotherapy. This simple, inexpensive biomarker holds considerable potential as a component of a multi-faceted prognostic model for NSCLC.